1971
DOI: 10.1111/j.1476-5381.1971.tb07216.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolonged treatment with tetracosactrin on hypothalamo‐pituitary‐adrenal function in the rat

Abstract: Summary1. The functional integrity of the hypothalamo-pituitary adrenal (HPA) system was assessed in rats after prolonged treatment with tetracosactrin. 2. Adrenal size and sensitivity to corticotrophin were increased. 3. Both the circadian rhythm and the stress-induced increase in HPA activity were inhibited. The circadian rhythm recovered before the response to stress. 4. Tetracosactrin given after betamethasone treatment delayed the return of a normal HPA response to stress. 5. Suppression of HPA activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…The action of chronic administration of dexamethasone to rats in the oestrous cycle on central PNMT activity appears to be dependent on the status and function of the hypothalamo-pituitary-adrenal function which has been shown to be impaired after therapy with corticosteroids or corticotrophin (37). These authors observed that beta methasone-treated rats showed adrenal atrophy and insensitivity to exogenous cor ticotrophin.…”
Section: Variations In Hypophysealsupporting
confidence: 56%
See 1 more Smart Citation
“…The action of chronic administration of dexamethasone to rats in the oestrous cycle on central PNMT activity appears to be dependent on the status and function of the hypothalamo-pituitary-adrenal function which has been shown to be impaired after therapy with corticosteroids or corticotrophin (37). These authors observed that beta methasone-treated rats showed adrenal atrophy and insensitivity to exogenous cor ticotrophin.…”
Section: Variations In Hypophysealsupporting
confidence: 56%
“…These authors observed that beta methasone-treated rats showed adrenal atrophy and insensitivity to exogenous cor ticotrophin. In addition to this, similar treat ment with the synthetic corticoid prevented the normal circadian rhythm and the stress induced rise in plasma corticosterone con centration (37). The impairment of hypo thalamo-pituitary-adrenal function resulting from chronic dexamethasone administration prevents the mobilization of endogenous corticotrophin which is required to maintain normal corticosterone levels in the plasma as well as in the central nervous system.…”
Section: Variations In Hypophysealmentioning
confidence: 99%